The impact on the cost of making high pressure die castings with multi-cavity die and vacuum assistance. (April 2023) - Dudek, Piotr; Białoń, Joanna; Piwowońska, Justyna; Walczak, Wiesław; Wrzała, Konrad
Abstract: In view of the increasing prices of energy and charge materials, it is necessary to optimize the costs of making castings. Tests were carried out on the possibility of making castings in a pressure die with an increased number of cavities with the required tightness of the casting. The tests were carried out on castings made in the High Pressure Die Casting process and with the use of the Vacuum System. The research included optimization of the pressure die design through selection of casting parameters and CT tests and microstructure. The results of the tests showed that it is possible to increase the number of pressure die cavities and to obtain the required level of casting porosity, provided that the Vacuum system is used. The amount of gas porosity in castings can be significantly reduced from 4% at atmospheric pressure to 1% at a vacuum of 300 mbar. Highlights: Vacuum Assisted High Pressure Die Casting, Porosity, Microstructure, Aluminium alloys, Cost die casting parts.